Evaluation of Glucose-6-phosphate dehydrogenase stability in stored blood samples - Jalil N.; Azma R.Z.; Mohamed E.; Ithnin A.; Alauddin H.; Baya S.N.; Othman A. (Leibniz Research Centre for Working Environment and Human Factors, 2024)
Glucose-6-Phosphate Dehydrogenase (G6PD) deficiency is the commonest cause of neonatal jaundice in Malaysia. Recently, OSMMR2000-D G6PD Assay Kit has been introduced to quantitate the level of G6PD activity in newborns delivered in Universiti Kebangsaan Malaysia Medical Centre (UKMMC). As duration of sample storage prior to analysis is one of the matters of concern, this study was conducted to identify the stability of G6PD enzyme during storage. A total of 188 cord blood samples from normal term newborns delivered at UKMMC were selected for this study. The cord bloods samples were collected in ethylene-diamine-tetra-acetic acid (EDTA) tubes and refrigerated at 2-8 C. In addition, 32 out of 188 cord blood samples were spotted on chromatography paper, air-dried and stored at room temperature. G6PD enzyme activities were measured daily for 7 days using the OSMMR2000-D G6PD Assay Kit on both the EDTA blood and dried blood samples. The mean value for G6PD activity was compared between days of analysis using Student Paired T-Test. In this study, 172 out of 188 cord blood samples showed normal enzyme levels while 16 had levels corresponding to severe enzyme deficiency. The daily mean G6PD activity for EDTA blood samples of newborns with normal G6PD activity showed a significant drop on the fourth day of storage (p < 0.005) while for samples with severely deficient G6PD activity, significant drop was seen on third day of storage (p = 0.002). Analysis of dried cord blood showed a significant reduction in enzyme activity as early as the second day of storage (p = 0.001). It was also noted that mean G6PD activity for spotted blood samples were lower compared to those in EDTA tubes for all days (p = 0.001). Thus, EDTA blood samples stored at 2-8 C appeared to have better stability in terms of their G6PD enzyme level as compared to dried blood samples on filter paper, giving a storage time of up to 3 days. 2016, Leibniz Research Centre for Working Environment and Human Factors. All rights reserved.